A design-based approach to bridging the gap between university learning and classroom pedagogy in Initial Teacher Education - Reece Sohdi (Journal of Learning Development in Higher Education)
This article explores the design, implementation, and evaluation of the Passports tool, developed to address the persistent challenge of bridging theoretical knowledge with practical application in Initial Teacher Education (ITE). Grounded in Design-Based Research (DBR), the Passports were iteratively created to integrate academic and professional literacies through two key components: ‘Learn That’ knowledge organisers and ‘Learn How To’ infographics. These elements provide trainees with structured support for consolidating theoretical concepts and applying them in diverse, real-world teaching contexts. Drawing on frameworks such as cognitive load theory, situated learning, and reflective practice, the Passports aim to foster adaptive expertise and reflective skills, supporting trainees as they navigate the complexities of professional placements.